Records of new algal taxa within various aquatic and aerophytic habitats in Slovenia - Aleksandra Krivograd Klemenčič; Mihael J. Toman; Damjan Balabanič (Natura Sloveniae, 2009)
In Slovenia, the first algal research dates back to the year 1845, when Kützing referred to several localities in Slovenian territory in his work »Phycologia germanica«. The present knowledge of diversity, variety and abundance of algae, however, is still incomplete, which applies both to aquatic and terrestrial species. The presented study carried out in 2005 and 2006 included 30 different aquatic and 5 terrestrial environments. It embraced data on species composition and distribution of benthic species in aquatic ecosystems and terrestrial environments. 634 taxa from ten classes were identified, 170 of which were discovered in Slovenia for the very first time. Most new identified taxa in Slovenia belong to Bacillariophyceae, specifically Navicula and Nitzschia. The genera of Amphidinium, Bumilleria, Heterothrix, Stylopyxis, Entomoneis, Stenopterobia, Chlorophysema, Podohedra and Poloidion had not been recorded in Slovenia prior to this study.